1770 N.C. Sess. Laws 787-88 - (:unkn) unknown (My University, 1770)
Eliminated a conscientious objector exemption and ordered "all Male Persons of the people called Quakers, between the age of Sixteen and Sixty" to enlist in the militia. Additionally, the act provided that "the Father or where there is no Father living, the Mother of each and every Person under the age of Twenty One Years, shall be liable to the Payment of the Fines becoming due from their respective sons so under age."
Keywords: MILITIAS